Accelerated hypofractionated radiotherapy with 3 Gy per fraction for central/ultra-central lung tumors: toxicity to mediastinal organs. (6th December 2022) - Ito, Kei; Minakami, Shota; Nakajima, Yujiro; Karasawa, Katsuyuki
Abstract: Background: Accelerated hypofractionated radiotherapy with 3 Gy per fraction is routinely performed for central lung tumors in Japan. However, the tolerable doses to mediastinal organs at risk during this procedure are unclear. This study aimed to clarify the rate of toxicities and tolerable doses to mediastinal organs. Methods: Patients treated with accelerated hypofractionated radiotherapy using a total dose of 60–75 Gy, with 3 Gy per fraction, for central lung tumors (July 2009–April 2021) were retrospectively reviewed. We extracted patients who received ≥30 Gy irradiation to each mediastinal organ and analyzed dosimetric factors, including doses to 0.03, 0.5, 1, 4 and 10 mL of each organ, in relation to grade 3–5 toxicities, except for radiation pneumonitis. Results: In total, 251 organs in 91 (ultra-central, 24) lesions were analyzed, with a median follow-up duration of 26 months (range, 4–94). The prescribed doses were 75/72/69/66/63/60 Gy for 52/14/16/3/2/4 lesions, respectively. Grade 3 bronchopulmonary hemorrhage was confirmed in two (2.2%) patients, whose tumors were located ultra-centrally. The two patients with toxicity received up to 74.5 and 71.6 Gy to the bronchus. Among patients who received 70 Gy or more to the bronchus, the incidence rate was 7% (2/28 patients). Conclusion: The rate of severe toxicities was low (2.2%). Although we did not identify the dose tolerance of the organs, because of the low incidence rate, we did note that doses of >70 Gy to the bronchus were likely to cause bronchopulmonary hemorrhage. Abstract : We evaluated the toxicity of accelerated hypofractionated radiotherapy for central lung tumors. The rate of severe toxicities was low (2.2%). The recommended threshold is 70 Gy to avoid bronchopulmonary hemorrhage.